The psychosocial experience of high school girls highly susceptible to stereotype threat: A phenomenological study. Issue 6 (1st November 2016) - Picho, Katherine
ABSTRACT: The author used phenomenology to explore the subjective experience of ninth-grade girls susceptible to mathematics-related stereotype threat in their authentic learning environments. The sample constituted students categorized as either having low or high susceptibility to stereotype threat (SST) enrolled in Honors mathematics classes at an urban high school in the Northeast United States. Results showed that high-SST students experienced a wide range of negative emotions regarding both mathematics and its learning context. Emotions commonly experienced by this group included low self-efficacy and hopelessness specific to learning mathematics, frustration, and feelings of isolation (both social and intellectual) in their classes. Experiences common to these students were perceived differential teacher treatment, and stereotype endorsement linking mathematics ability to fixed traits such as race or genetics. Low-SST students, on the other hand, experienced positive relationships with their teachers, positive schooling experiences, and a malleable view of intelligence.